Supervising Master’s Thesis in English-Medium Programs in Public Universities in Azerbaijan: Roles, Responsibilities, and Models - Vahidzada, Latifa (ADA University, 2023)
The study aimed to explore master’s degree student’s and master’s thesis supervisors’ perceptions of the supervision process, supervisors’ roles, and their responsibilities in English medium programs in Azerbaijani public higher education institutions (HEIs). Although supervision was a well-explored process in Western and Asian countries, this topic had never been investigated in Azerbaijan. Therefore, state policies and resolutions on higher education have been reviewed to get initial data regarding the phenomenon. Moreover, semi-structured interviews were conducted to collect data from the eighteen participants. For this purpose, nine master’s degree students and nine supervisors of those students in three public HEIs were interviewed. According to the findings of the study, most participants stated that the master’s degree students chose their thesis titles and thesis supervisor at the beginning of the second term. Furthermore, the findings showed that nearly the majority of master’s thesis supervisors did not require a plan for the thesis from their students. Instead, supervisors provided students with a plan based on the university guidelines regarding master’s thesis dissertations. The most common supervisory roles listed by supervisors were a guide, a supporter, a friend, a teacher, and an academic advisor. Likewise, graduate students expressed a role of a supporter, a guide, a helper, and a motivator which they considered more relevant to their supervisors. When it comes to the findings regarding supervisors’ responsibilities, they were regarded as ensuring a good quality thesis, suggesting literature, reminding students of deadlines, meeting students’ needs, being available for meetings, and providing academic and emotional support. Based on the findings, neither supervisors nor students were aware of the supervision models in literature which were anticipated before the data collection process; however, the supervisors utilized particular strategies that had been shaped during the practice. Most supervisors stated that they supported and guided students when they needed help as an indication of the Apprenticeship model. Nevertheless, they occasionally assisted students with academic writing and organizational skills meaning the Teaching model of supervision was utilized in some cases in Azerbaijani public HEIs.
Keywords: Graduate students -- Supervision of -- Azerbaijan; Theses -- Supervision -- Higher education; Teacher-student relationships -- Azerbaijan; Education